Optoelectronic Simulations of InGaN-Based Green Micro-Resonant Cavity Light-Emitting Diodes with Staggered Multiple Quantum Wells - Tsau-Hua Hsieh; Wei-Ta Huang; Kuo-Bin Hong; Tzu-Yi Lee; Yi-Hong Bai; Yi-Hua Pai; Chang-Ching Tu; Chun-Hui Huang; Yiming Li; Hao-Chung Kuo (Crystals, 2023)
In this research, we compared the performance of commercial μ-LEDs and three-layered staggered QW μ-LED arrays. We also investigated the self-heating effect. We proposed a green micro-resonant cavity light-emitting diode (µ-RCLED) that consists of a three-layer staggered InGaN with multiple quantum wells (MQWs), a bottom layer of nanoporous n-GaN distributed Bragg reflectors (DBRs), and a top layer of Ta2O5/SiO2 DBRs. We systematically performed simulations of the proposed µ-RCLEDs. For the InGaN MQWs with an input current of 300 mA, the calculated wavefunction overlaps are 8.8% and 18.1% for the regular and staggered structures, respectively. Furthermore, the staggered MQWs can reduce the blue-shift of electroluminescence from 10.25 nm, obtained with regular MQWs, to 2.25 nm. Due to less blue-shift, the output power can be maintained even at a high input current. Conversely, by employing 6.5 pairs of Ta2O5/SiO2 DBRs stacks, the full width at half maximum (FWHM) can be significantly reduced from 40 nm, obtained with ordinary µ-LEDs, to 0.3 nm, and a divergence angle smaller than 60° can be obtained. Our simulation results suggest that the µ-RCLEDs can effectively resolve the wavelength instability and color purity issues of conventional µ-LEDs.